Influence of Salinity on Physiological Response of the Bearded Horse Mussel Modiolus barbatus and Noah’s Ark Shell Arca noae - Vlašić Matea; Glavić Nikša; Bolotin Jakša; Hrustić Enis; Radić Iris Dupčić (Ekológia (Bratislava), 2018)
Bearded horse mussel Modiolus barbatus and Noah’s ark shell Arca noae are a species of interest for the diversifying shellfish aquaculture on the south-eastern coast of the Adriatic. In this study, oxygen consumption (OC), total ammonia excretion (TAM) and clearance rate (CR) responses to the changes in seawater salinity (37, 30, 25 and 20) were investigated in the laboratory. There is a statistically significant influence of salinity on oxygen consumption and TAM excretion of Noah’s ark shell, while the time of exposure to different salinities is significantly correlated to TAM excretion by the bearded horse mussel. Mean OC of Noah’s ark shell ranged from 0.14 ± 0.06 to 0.54 ± 0.27 mg O2g−1h−1 and that of bearded horse mussel from 0.18 ± 0.17 to 0.26 ± 0.14 mg O2g−1h−1. Mean values of TAM excretion of Noah’s ark shell ranged from 2.14 ± 1.52 to 7.22 ± 6.04 μmol g−1 h−1 and for bearded horse mussel from 0.98 ± 0.53 to 2.78 ± 2.96 μmol g−1 h−1. Salinity and exposure time have a significant influence on the CR of Noah’s ark shell, whilst salinity has been found to be the determining factor for the bearded horse mussels’ CR. Mean values of Noah’s ark shell CR ranged from 0.96 ± 0.54 to 4.18 ± 1.15 l h−1g−1 and for bearded horse mussel from 2.43 ± 0.99 to 4.23 ± 0.84 l h−1g−1. Higher oxygen consumption to total ammonia excretion (O:N) ratios at lower salinities indicated the use of proteins as a metabolic substrate for both species. Noah’s ark shell has greater energy expenditure related to respiration and TAM excretion than the bearded horse mussel.